Efficiency comparison of fin heatsink models using solidworks thermal analysis - Angga Hermawansyah; Andre Kurniawan; Sein Laer Yi Win; Nanang Qosim; Syamsul Bahri Biki; Apri Wiyono (Researcher and Lecturer Society, 2023)
Heatsink is composed of square or circular-shaped base plates connected to fins on one side. Fluid flow within the heatsink typically occurs through natural convection, where colder air flows into the hotter fin region and exits through the fin tips. In this study, we conducted numerical simulations using Solidworks 2021-2022 Research Licence software to investigate three different heatsink models with distinct shapes, aiming to determine the most effective cooling rate. The thermal simulation results revealed that the heatsink design with square fins exhibited lower maximum temperatures, making it recommended for applications utilizing natural convection. Additionally, heat sinks with thinner fins have a larger surface area, accommodating more fins compared to thicker ones, which affects the heat transfer efficiency within the heat sink.